Crisis and extended realities: remote presence in the time of COVID-19. (February 2021) - Matthews, Benjamin; See, Zi Siang; Day, Jamin
The transformative influence of the COVID-19 pandemic on remote forms of communication has been a frequent theme in popular discourse during 2020, but any lingering transformation of what we do at a distance will rely on convincing and accessible forms of remote presence and interaction. Embodied communication is difficult to simulate, and this discussion examines current and emerging extended reality (XR)–based communication tools in a range of contexts to discover what role they may play in a future where crises of mobility are likely to grow more frequent and protracted. We define XR and its current uses, then examine key terms used to conceptualise it such as 'presence' and 'social presence', before highlighting social challenges of remote presence and ethical considerations that accompany its use, particularly how the technology might (or fail to) address important social problems, support education and have relevance to the future of work.